Exoskeleton Training for Spinal Cord Injury Neuropathic Pain (ExSCIP): Protocol for a Phase 2 Feasibility Randomised Trial [version 1; peer review: 1 approved, 2 approved with reservations] - Orlaith Doherty; Conor White; Nanna Brix Finnerup; Eimear Smith; Mark Pollock; Nathan Kirwan; Olive Lennon; Catherine Blake (HRB Open Research)
Background Following Spinal Cord Injury (SCI), 53% of people develop neuropathic pain (NP). NP can be more debilitating than other consequences of SCI, and a persistent health issue. Pharmacotherapies are commonly recommended for NP management in SCI, although severe pain often remains refractory to these treatments in many sufferers. Furthermore, poor medication adherence exists, stemming from unacceptable side-effects and fear of dependency. Sensorimotor stimulation using active walking with robotic assistance has not been well studied in NP after SCI, despite convincing locomotor-based pre-clinical studies, identifying prevention and reversal of NP. Our primary aim is to assess the impact of exoskeleton-based walking on NP intensity and interference after SCI and examine feasibility outcomes for progression to a definitive trial. Methods This is a phase 2 single-blinded, randomised feasibility study. It will test the feasibility and acceptability of exoskeleton-based walking 3 times per week for 12 weeks (intervention), as a mechanistic-based intervention for NP after SCI. The comparator will be an equally dosed, blended relaxation programme devoid of motor imagery prompts. 40 participants with moderate-to-severe NP post SCI will be recruited and randomised to intervention and comparator groups. The primary outcomes are feasibility outcomes for progression to definitive trial which include recruitment and retention rates, adverse events and acceptability of the intervention. Secondary outcomes explore changes in NP intensity and interference as measured by the International Spinal Cord Injury Pain Basic Data Set 3.0 (ISCIPBDS) at baseline, post-intervention (week 13) and at 6-month follow-up. Conclusions There is a need to explore non-pharmacological management of NP after SCI. The findings of this feasibility trial will inform the development of a future multicentre, international RCT, Trial Registration NCT06463418, 08/07/2024, https://clinicaltrials.gov/study/NCT06463418.